Mycotoxicological properties of fusarium verticillioides and the fumonisins : mechanisms and implications for setting risk assessment parameters in humans - Gelderblom, Wentzel Christoffel Andreas (Stellenbosch : Stellenbosch University, 2009)
Thesis (DSc (Biochemistry))--Stellenbosch University, 2009.